Efektivitas Mahkamah Syariah dalam Penegakan Qanun Jinayat di Aceh - Tiara Putri Ayu Setyaningrum; M. Junaidi (Mahkamah : Jurnal Riset Ilmu Hukum, 2026)
The Aceh Sharia Court has special authority to enforce Qanun Jinayat as part of the implementation of Aceh's privileges in the legal field. This research aims to analyze the effectiveness of the Sharia Court in enforcing Qanun Jinayat in Aceh. The research method used is normative legal research with a statutory regulatory approach and a conceptual approach. The research results show that the Sharia Court has carried out judicial functions in accordance with its authority in examining, adjudicating and deciding jinayat cases. The research results reveal that the effectiveness of enforcing Qanun Jinayat still faces a number of obstacles, including limited resources of the judicial apparatus, differences in public understanding of jinayat law, and coordination between law enforcers that is not yet optimal. This research concludes that the Sharia Court functions in enforcing Qanun Jinayat, but it requires improving institutional quality and legal system support so that the objectives of enforcing sharia law can be achieved optimally.